1981
DOI: 10.2134/agronj1981.00021962007300050024x
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Comparison of Senescent and Nonsenescent Sorghum Genotypes1

Abstract: Under normal field conditions, leaves of many typical sorghum [Sorghum bicolor (L.) Moench] lines such as BT×378, RT×7000, RT×2536, and SC 214(IS 1598C) senesce after grain maturity. In the field, several upper leaves of three partially converted lines [SC0056 (IS 12568), SC0599 (Rio), and SC0170 (IS12661)] from the sorghum conversion program remained green and apparently vigorous after grain maturity. This phenomenon of green leaf retention after the grain reached physiological maturity was termed “nonsenesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 9 publications
1
43
0
4
Order By: Relevance
“…This clearly demonstrates the significance of leaf area duration in yield determination in wheat. Our results are in accordance with the earlier reports of Duncan et al (1981), Rosenow et al (1983) Ludlow and Muchow (1990) and Ashraf et al (1992).…”
Section: Plant Growth and Developmentsupporting
confidence: 94%
“…This clearly demonstrates the significance of leaf area duration in yield determination in wheat. Our results are in accordance with the earlier reports of Duncan et al (1981), Rosenow et al (1983) Ludlow and Muchow (1990) and Ashraf et al (1992).…”
Section: Plant Growth and Developmentsupporting
confidence: 94%
“…São vários os caracteres que se encontram associados com o porte mais ereto, dentre eles o fenótipo denominado stay green (DUNCAN et al, 1981). Há consenso entre os melhoristas que o fenótipo stay green é importante para assegurar plantas mais eretas, principalmente porque a senescência do caule é mais tardia, só ocorrendo após a maturação fisiológica das vagens.…”
Section: Introductionunclassified
“…É verificado em milho, sorgo e girassol que as cultivares com stay green são mais resistentes ao acamamento e ao estresse hídrico, além de serem mais tolerantes a pragas e doenças (DUNCAN et al, 1981). No feijão há informações sobre o controle genético do stay green que indicam um número pequeno de genes, embora o caráter possua elevada sensibilidade ao ambiente (AGUIAR et al, 2000).…”
Section: Introductionunclassified
“…For instance, similar to the present study (Table 4), Hooker (1985) found a decrease in head weight and weight of the 100 seeds associated with reduction in soil moisture by affecting grain filling. In their comparative study of senescent and non-senescent sorghum genotypes, Duncan et al (1981) also found that the non-senescent (stay-green) genotypes had higher test weight. However, genotypic differences do exist for the period they take to fill their grain due to their efficiency in using the available moisture during post anthesis deficit.…”
Section: Yield and Yield Attributesmentioning
confidence: 96%